LEGO Harry Potter ideas book - Dolan, Hannah; March, Julia (DK Publishing, 2023)
Delve into the world of LEGO Harry Potter and be inspired to build your own magical creations with LEGO Harry Potter Ideas Book, packed full of model ideas and expert tips. Inspirational images, model breakdowns, and descriptive text make it easy for fans of all ages to jump in and begin building.